Intraspecies Polymorphisms in the Lipophosphoglycan of L. braziliensis Differentially Modulate Macrophage Activation via TLR4 - Vieira, Tamara da Silva; Rugani, Jeronimo Nunes; Nogueira, Paula Monalisa; Torrecilhas, Ana Cláudia; Gontijo, Celia Maria Ferreira; Descoteaux, Albert; Soares, Rodrigo Pedro (Frontiers in Cellular and Infection Microbiology, 2019)
Lipophosphoglycan (LPG) is the major Leishmania surface glycoconjugate having importance during the host-parasite interface. Leishmania (Viannia) braziliensis displays a spectrum of clinical forms including: typical cutaneous leishmaniasis (TL), mucocutaneous (ML) and atypical lesions (AL). Those variations in the immunopathology may be a result of intraspecies polymorphisms in the parasite’s virulence factors. In this context, we evaluated the role of LPG of strains originated from patients with different clinical manifestations and the sandfly vector. Six isolates of L. braziliensis were used: M2903, RR051 and RR418 (TL), RR410 (AL), M15991 (ML) and M8401 (vector). LPGs were extracted and purified by hydrophobic interaction. Peritoneal macrophages from C57BL/6 and respective knock-outs (TLR2 -/- and TLR-4 -/-) were exposed to different LPGs for nitric oxide (NO) and cytokine production (IL-1beta, IL-6, IL-12 and TNF-alpha). LPGs differentially activated the production of NO and cytokines via TLR4. In order to confirm if such functional variations were related to intraspecies polymorphisms in the LPG, the purified glycoconjugates were subjected to western blot with CA7AE and LT22. Based on antibody reactivity preliminary variations in the repeat units were detected. To confirm these findings, LPGs were depolymerized for purification of repeat units. After thin layer chromatography, intraspecies polymorphisms were confirmed especially in the type and/size of sugars branching-off the repeat units motif. In conclusion, different isolates of L. braziliensis from different clinical forms and hosts can induce different responses in cells of the vertebrate host and this could be a result of LPG polymorphisms.